2022
DOI: 10.4103/aja2021103
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of SARS-CoV-2 RNA shedding in semen of 36 males with symptomatic, asymptomatic, and convalescent infection during the first and second wave of COVID-19 pandemic in Italy

Abstract: The severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2) receptor, angiotensin-converting enzyme 2 (ACE2), has been identified in the human testis, but the risk of transmission of SARS-CoV-2 through sexual intercourse still needs to be defined. The goal of our study was to determine if SARS-CoV-2 is detectable in the semen of patients suffering or recovering from coronavirus disease-19 (COVID-19), still testing positive at nasopharyngeal swabs but showing mild or no symptoms at the time of sampling. De… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 30 publications
0
1
0
Order By: Relevance
“…Several studies have documented the shedding of SARS-CoV-2 in the semen of men with symptomatic and asymptomatic phases [47,48]. In contrast, other investigators were unable to detect virus particles in the semen of men infected with SARS-CoV-2 [49][50][51]. Hence, the detection of viruses in semen samples remains debatable.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have documented the shedding of SARS-CoV-2 in the semen of men with symptomatic and asymptomatic phases [47,48]. In contrast, other investigators were unable to detect virus particles in the semen of men infected with SARS-CoV-2 [49][50][51]. Hence, the detection of viruses in semen samples remains debatable.…”
Section: Discussionmentioning
confidence: 99%
“…Angiotensin-converting enzyme 2 (ACE2)-the receptor that has a role in SARS-CoV-2 invasion-is highly expressed in the genitourinary tract and the testes [4,5]. Studies have reported that SARS-CoV-2 is not present in the semen of individuals recovering from COVID-19 [6] or patients with a mild form of COVID-19 in their acute stage of the disease [7]; furthermore, some other results implied that the detection of viral RNA of SARS-CoV-2 is actually rare in semen, yet its RNA could be found in semen even in a small sample size [5,8].…”
Section: Introductionmentioning
confidence: 99%